Finite Element Analysis of a Portal Frame Subjected to Concentrated Impulse Loading - Wong, Choon Yap (2009)
In general, the portal frame structure which undergoing a large deflection will be studied more on how the structure response upon subjected to dynamic impact loading. In this project we are studying the different material constitutional model to simulate the response effect by using finite element analysis. During the simulation process, the most influent geometry parameters such as width, height, thickness are being simulated by ANSYS LS-DYNA finite element commercial software. By using the finite element commercial software, the response mode of the portal frame will be captured and compared with experimental results. The output solutions such as stress, strain and displacement effects will be studied and discussed. This finite element impact modeling is being model by generating the SHELL elements as a portal frame and the SOLID element as a projectile. In this project, this portal frame is made up by a square rectangular frame of aluminium sheet with the portal width of 5.2” and the portal height of 4.6” with both support column were clamp permanently. Meanwhile, the portal wide strip of 0.5” with a thickness of 0.036” will be developed for this finite element modeling analysis. The portal frame meshing consists of portal frame with 28 elements and 58 nodes, while the impact projectile consists of 143 elements and 245 nodes. Besides, the classifications of impact types also being study by this project in general. Results obtain in this study shown that by employing a different material model to simulate the impact, we can uses the different material model to predict the large deformation, stress distribution, strain distribution and displacement distribution as comparison to experimental results. In addition, by adjusting width and height ratio of the portal frame, the results can be used to optimization the best impact resistant structures and this could be used in themore complex portal frame for future study.